Fates and furies - Groff, Lauren (New York : Riverhead Books, 2015)
Every story has two sides. Every relationship has two perspectives. And sometimes, the key to a great marriage is not its truths but its secrets. At age twenty-two, Lotto and Mathilde are tall, glamorous, madly in love, and destined for greatness. A decade later, their marriage is still the envy of their friends, but with an electric thrill we understand that things are even more complicated and remarkable than they have seemed.
Keywords: Married people -- Drama; Truthfulness and falsehood -- Drama; Domestic fiction; Love stories